2021
DOI: 10.1186/s40550-021-00081-2
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide traces in local crops of Sancti Spíritus, Cuba: risk assessment study

Abstract: Background Vegetables and rice produced in Cuba may contain residue of pesticides that exceed the maximum residue limits (MRLs). Pesticide residues on crop samples from Sancti Spíritus province were analyzed. Based on these residue data, a risk assessment of consumer exposure was conducted. Methods Samples collected during the 2017, 2018, and 2019 periods were analyzed using UPLC-MS/MS and GC/ECD chromatography techniques. A deterministic risk asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Many pesticides were detected in all studied fruits and vegetables with levels below the EU MRLs except for Fonofos, fenitrothion and fenhexamid. Our ndings are consistent with existing literature showing detection of many pesticides in fruits and vegetables [50,51,55,56]. Like our ndings, many past studies have pesticide residue levels that are above MRL values, especially organophosphates like fenitrothion [46,48,53,54,[57][58][59][60].…”
Section: Discussionsupporting
confidence: 92%
“…Many pesticides were detected in all studied fruits and vegetables with levels below the EU MRLs except for Fonofos, fenitrothion and fenhexamid. Our ndings are consistent with existing literature showing detection of many pesticides in fruits and vegetables [50,51,55,56]. Like our ndings, many past studies have pesticide residue levels that are above MRL values, especially organophosphates like fenitrothion [46,48,53,54,[57][58][59][60].…”
Section: Discussionsupporting
confidence: 92%
“…This acaricide and fungicide were only detectable in the Pakistani group, which was below the ISIRI permissible limit (0.05 mg kg −1 ). Additionally, López-Dávila et al [ 50 ] observed no chlorothalonil contamination in their rice sample in Cuba. Generally, the most appropriate status of pesticide contamination belonged to Thai samples with no detectable concentration of pesticides.…”
Section: Resultsmentioning
confidence: 96%